In vivo evidence for pre‐symptomatic neuroinflammation in a MAPT mutation carrier. Issue 2 (2nd January 2019) - Bevan‐Jones, W. Richard; Cope, Thomas E.; Jones, P. Simon; Passamonti, Luca; Hong, Young T.; Fryer, Tim; Arnold, Robert; Coles, Jonathan P.; Aigbirhio, Franklin I.; O'Brien, John T.; Rowe, James B.
Abstract: Neuroinflammation occurs in frontotemporal dementia, however its timing relative to protein aggregation and neuronal loss is unknown. Using positron emission tomography and magnetic resonance imaging to quantify these processes in a pre‐symptomatic carrier of the 10 + 16 MAPT mutation, we show microglial activation in frontotemporal regions, despite a lack of protein aggregation or atrophy in these areas. The distribution of microglial activation better discriminated the carrier from controls than did protein aggregation at this pre‐symptomatic disease stage. Our findings suggest an early role for microglial activation in frontotemporal dementia. Longitudinal studies are needed to explore the causality of this pathophysiological association.